A novel second-order output spectrum based local tuning method for locating bolt-loosening faults. (15th January 2021) - Li, Quankun; Jing, Xingjian
Highlights: Inherent material or boundary nonlinearities and multiple faults are considered in fault localization. A more reliable and sensitive second-order output spectrum (SOOS) based fault indicator is established. A novel local tuning approach (LTA) is proposed for detecting more local and sensitive fault features. Numerical and experimental results validate the effectiveness of the proposed method. Abstract: This paper presents a novel second-order output spectrum (SOOS) based method with a local tuning approach (LTA) for the precise localization of multiple bolt-loosening faults in complex structures with a simple sensor chain. The development of this new method is based on a recently developed virtual beam-like structure (VBLS) concept and the nth-order output spectrum estimation (nth-OSE) algorithm using only properly measured data. In this new method, a more general multi-degree-of-freedom (MDOF) model with general nonlinear restoring forces, caused by not only faults but also inherently existing material or boundary nonlinearities in structures, is considered, and a special local tuning mechanism is intentionally proposed to derive the novel SOOS based damage indicator. Results of numerical and experimental studies demonstrate that this novel SOOS based local tuning method can give more accurate, sensitive and reliable information about fault positions, and then can be used effectively and reliably for the precise localization of multiple bolt-loosening faults in complex structures even with inherent material or boundary nonlinearities. The results of this study would present a totally new insight into initial structural fault detection by employing sensitive nonlinear features from a systematic frequency domain approach.